(untitled) (Vallis Aurea, 2024)
Based on the standard vector error correction model with quarterly data, this study focuses on the relationship between inflows of exports, foreign investments together with Gross Domestic Product, of the last decades in Albania to research in both the short-run dynamics and the long-run trends. Using diverse secondary data with differing methods of data collection over time and especially dealing with data collected during the economic transition period, presents a challenge in terms of reliability of the data that can lead thus to studies which may result in controversial conclusions for the same country. The impulse analysis reveals that foreign direct investment inflows cause an almost negligible (positive) fluctuation in exports and a (negative) fluctuation in GDP in the long run. Conversely, exports, after a short-term negative impact, lead to an increase in FDI inflows in the long run and a slight increase in the GDP level. Finally, GDP has a positive effect on both variables. The result, therefore, is very important as it suggests that the government should focus on openness, growth and exports—devaluating thus the role of FDI inflows, at least in the short term.